Deskripsi Kemampuan Peserta Didik Menyelesaikan Soal HOTS Materi Pecahan Dikaji dengan Kemandirian Belajar Kelas V SD - Wulan Suci; Hery Kresnadi; Bistari Bistari; Kartono Kartono; Dyoty Auliya Vilda Ghasya (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2023)
The purpose of this study was to describe the ability of students to solve HOTS questions examined by the independence of students in the high, medium and low groups. This research is a qualitative descriptive study. The subjects of this study were 6 students who represented each group's ability to solve problems. Data collection uses HOTS test questions, observation sheets, interviews and documentation. HOTS questions totaling 5 questions were adopted and validated by material experts. The ability of students to solve HOTS questions assessed by learning independence will be described based on the problem solving stage, namely understanding the problem, designing a problem solving strategy, carrying out a calculation plan, and re-evaluating the correctness of the results obtained. The results of the study concluded that students were able to solve HOTS questions of addition and subtraction of fractions with different denominators and were in line with the independent attitude of students' learning, namely having a very good attitude, in which students in the high group showed a tendency to have very good self-confidence, the ability of students the group is solving HOTS questions on addition and subtraction material studied by learning independence in class V. And in line with the attitude of learning independence which is good, in which students in the medium group tend to show a good attitude of independence as well and the ability of low group participants to solve HOTS questions in addition and subtraction material was studied with independent learning for class V. Students were unable to complete HOTS on addition and subtraction material with different denominators because they were unable to fulfill all the ways of solving problems. And in the attitude of self-reliance in learning, students in the low group tend to show that they have an attitude of independence that is sufficient, some even less.